Effect of Peer Work Performance on the Focal Employee's Voice Taking: The Role of Trust and Self-Construal. Issue 2 (April 2021) - Zhang, Guanglei; Chen, Silu
Based on persuasion theory, this study examines the influence of peer work performance on the focal employee's voice-taking relationship. Our study purposes that peer work performance contributes to the focal employee's cognition-based trust and that their interdependent self-construal moderates this relationship. Our study suggests that cognition-based trust mediates the relationship between peer work performance and the focal employee's voice taking. Finally, we intend to show that the focal employee's interdependent self-construal moderates the mediating role of cognition-based trust in transmitting the effect of peer work performance on the focal employee's voice taking. Analyses of the data collected from China support these hypotheses.